Impact of a high dietary fiber cereal meal intervention on body weight, adipose distribution, and cardiovascular risk among individuals with type 2 diabetes - Li, Xiaofeng; Shi, Yu; Wei, Dongqin; Ni, Wenyu; Zhu, Na; Yan, Xinyi (Frontiers in Endocrinology, 2023)
Objective: This study sought to examine the impacts of a high dietary fiber cereal meal in comparison to conventional dietary management for diabetes on body weight, distribution of adipose tissue, and cardiovascular risk among individuals diagnosed with type 2 diabetes (T2DM). Methods: A cohort of 120 patients diagnosed with T2DM was enlisted as the study population and divided into two groups using a ratio of 2:1—namely, the W group (n=80) and the U group (n=40). The U group (control) received usual diet, while the W group (intervention) incorporated a high dietary fiber cereal meal in place of their regular staple food in addition to adhering to conventional diabetes dietary recommendations. The high dietary fiber cereal meal was based on whole grains, traditional Chinese medicinal foods, and prebiotics. A subsequent follow-up period of 3 months ensued, during which diverse parameters such as body mass index (BMI),waist-hip ratio (WHR), glycated hemoglobin (HbA1c),fasting blood glucose(FBG),C-peptide levels, blood pressure, blood lipids, high-sensitivity C-reactive protein (hsCRP),10-year cardiovascular disease (CVD) risk, and Lifetime CVD risk were assessed before and after the intervention. Results: Among the participants, a total of 107 successfully completed the intervention and follow-up, including 72 individuals from the W group and 35 from the U group. Following the intervention, both cohorts exhibited decrease in BMI, WHR, HbA1c, FBG, blood pressure, and blood lipid levels in contrast to their initial measurements. Remarkably, the improvements in BMI, WHR, HbA1c, FBG, total cholesterol (TC), triglycerides(TG), low-density lipoprotein cholesterol (LDL-C), the ratio of triglyceride to high-density lipoprotein cholesterol (TG/HDL-C), and the ratio of 2-hour C-peptide (2hCP) to fasting C-peptide (FCP) were more marked within the W group, exhibiting statistically significant disparities (P<0.05) in comparison to the U group. Furthermore, the levels of hsCRP declined among individuals in the W group, while the U group experienced an elevation.10-year CVD risk reduction were similar in the two groups. While, Lifetime CVD risk only decreased significantly in the W group. Conclusion: The intervention centred on a cereal-based dietary approach showcased favourable outcomes with regard to body weight, adipose distribution, and cardiovascular risk in overweight individuals grappling with T2DM.